Neurotensin in the extended amygdala maintains wakefulness in novel environments - Chi Jung Hung; Shuhei Ueda; Sheikh Mizanur Rahaman; Mikiyasu Yamamoto; Jiahui Li; Noriaki Fukatsu; Haruhiko Bito; Hiroshi Yamaguchi; Akihiro Yamanaka; Sayaka Takemoto-Kimura; Daisuke Ono (Proceedings of the National Academy of Sciences, 2026)
Animals remain awake in unfamiliar environments to assess potential safety threats, a process involving changes in neuronal activity within sleep–wake regulatory brain regions. However, the specific circuits and neurotransmitters involved remain poorly understood. Here, we show that neurotensin (NTS) peptides in corticotropin-releasing factor (CRF) neurons of the lateral part of the interstitial nucleus of the posterior limb of the anterior commissure (IPACL) play a key role in maintaining wakefulness in response to environmental changes. Activation of IPACL CRF neurons increased wakefulness, whereas their inhibition or deletion of NTS reduced wakefulness in novel environments. These neurons are activated in response to exposure to a novel environment and project primarily to the substantia nigra pars reticulata (SNr) and release NTS, which modulates wakefulness. These findings suggest that NTS signaling from IPACL CRF neurons to the SNr is essential for sustaining wakefulness in unfamiliar or changing environments.